Efektivitas Perjanjian Perdagangan Bebas Indonesia Dalam Mengurangi Hambatan Perdagangan Serta Implikasinya terhadap Strategi Ekonomi Nasional - PM Erza Killian; Primadiana Yunita; Reza Triarda (Jayapangus Press, 2026)
Indonesia has signed multiple Free Trade Agreements (FTAs) to expand market access. However, the utilization rate of preferential tariffs remains low, while non-tariff barriers and rules of origin (ROO) complexity persist. This study aims to assess the effectiveness of Indonesia’s FTAs in reducing trade barriers, explain the implementation factors that make their impacts partial, and draw implications for Indonesia’s national economic strategy. Using a qualitative policy case study approach, the research combines semi-structured online interviews with eight officials from the Ministry of Trade and document analysis of FTA texts, implementing regulations, technical reports, and trade data; validity is strengthened through source triangulation. The findings show that FTAs have lowered tariffs and expanded market coverage to roughly 70% of Indonesia’s exports, yet the benefits have not been translated evenly across firms. Preferential use particularly among MSMEs is constrained by ROO compliance costs, documentation and input traceability burdens, post-shipment verification concerns, and divergent technical standards and certification requirements. Moreover, rising sustainability and labor compliance demands increase compliance costs, leaving de facto barriers significant even when preferential tariffs are available. FTA proliferation also generates a noodle bowl effect through overlapping rules and procedures, prompting firms to choose MFN tariffs when preferential savings do not justify administrative costs. The study concludes that FTA effectiveness depends critically on regulatory harmonization, simplification of preferential procedures, strengthened MSME compliance capacity, and enhanced digital trade facilitation to ensure more inclusive and sustainable gains.